Four Archetypes : (From Vol. 9, Part 1 of the Collected Works of C.G. Jung) [New in Paper]. - Jung, C. G. (Princeton University Press, 2012)
One of Jung's most influential ideas has been his view, presented here, that primordial images, or archetypes, dwell deep within the unconscious of every human being. The essays in this volume gather together Jung's most important statements on the archetypes, beginning with the introduction of the concept in "Archetypes and the Collective Unconscious." In separate essays, he elaborates and explores the archetypes of the Mother and the Trickster, considers the psychological meaning of the myths of Rebirth, and contrasts the idea of Spirits seen in dreams to those recounted in fairy tales. This.